Predicción del peso vivo a través del perímetro torácico en la raza bovina Lucerna (2002)
ABSTRACT: The objetive was to predict the body weight throught barimetry based on the chest girth by using measurments of 1273 animals of both sex with ages between one day and eigth years of the Lucerna breed. Regression analysis was made with the Gamma model (Y= AeBX XC + Ei ) and a equation was obtained to predict the body weight of this breed. Was realized a proof in order to demostrate the confiability of the predicted data. Results demostrated that there wasn‘t significant differences between the body weight measured and the body weight predicted with the equation.